(3EXgGQ eG cGf eSJNajkG aj CMcGe GdfLhes - (3fLe GdOjf CjhH Hf Yjf GdOhdI GdCNdGWis
(3ChdgG (B:s
(3HYO GdOjHGLg Efi JCedJ cJHG cKjQg ai Yde CMcGe GdfLhe ahLOJ CUhd GdCMcGe Ydi KeGfjI ChLg s
(3BNQgG (B:s
(3jfJgi Edi HYV GdLOGhd Yf GdPfH ai GdHQhL s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B10 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B40) s
Keywords: (3Gdadcs